2021
DOI: 10.1037/dhe0000189
|View full text |Cite
|
Sign up to set email alerts
|

Do diversity courses improve college student outcomes? A meta-analysis.

Abstract: Colleges and universities play a critical role in shaping intergroup dynamics in an era of increasing racial tensions in the United States. Diversity courses may serve as one important approach for preparing college students for participation in an equitable and just society, since this coursework holds a unique position at many institutions to expose college students to issues of difference and inequality. This study synthesizes research on the relationship between university/college instruction explicitly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Friendships matter too. Consistent with previous research on attitudes toward diversity (e.g., Denson et al, 2020;Ragin & Ehrhardt, 2020;Shim & Perez, 2018) and appreciation of Muslims (Abrams et al, 2018;Barlow et al, 2012;, this study reaffirmed the importance of meaningful relationships, exemplified by friendships, in fostering non-Muslims' appreciation. Non-Muslim students who did not make at least one Muslim friend during their first year in college, even if they had a Muslim friend before coming to college, did not increase in appreciation for Muslims.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Friendships matter too. Consistent with previous research on attitudes toward diversity (e.g., Denson et al, 2020;Ragin & Ehrhardt, 2020;Shim & Perez, 2018) and appreciation of Muslims (Abrams et al, 2018;Barlow et al, 2012;, this study reaffirmed the importance of meaningful relationships, exemplified by friendships, in fostering non-Muslims' appreciation. Non-Muslim students who did not make at least one Muslim friend during their first year in college, even if they had a Muslim friend before coming to college, did not increase in appreciation for Muslims.…”
Section: Discussionsupporting
confidence: 89%
“…Denson and colleagues (2020) reviewed research on diversity courses that spanned 25 years and found an overall small positive association between diversity coursework and positive outcomes related to the appreciation of others. Despite that small positive effect, Denson et al (2020) asserted that "infusing diversity throughout the curriculum-which could occur via some 'formal' diversity coursework and other courses that contain diversity content may constitute the most effective strategy for bolstering student growth" (p. 8). In another study, Shim and Perez (2018) showed that the number of academic courses focused on diversity and taken during the first year was not correlated to students' openness to diversity and challenge.…”
Section: Interfaith Engagement and Attitudinal Changementioning
confidence: 99%
“…While calls for "decolonizing the curriculum" have been widespread, social work education in particular needs to include more content related to anti-racism and antioppressive social work practice, including readings from BIPOC scholars. Emerging research shows that diversity coursework has an overall small but positive association on behavior, behavioral intent, affect, cognition, and diversity (Denson et al, 2020). By examining the curricula to assess the content and the extent to which Whiteness is centered explicitly and implicitly, we can broaden curricula to include counter-storytelling (Ortega & Feagin, 2016).…”
Section: Infuse Anti-racist Content Into Social Work Curriculamentioning
confidence: 99%
“…First, the higher education literature has shown the role of exposure to diverse ideas, cultures, and values through course curriculum in reducing prejudice and improving intergroup attitudes as well as academic benefits (Bowman, 2010; Denson, 2009; Denson et al., 2020; Nelson Laird et al., 2005). Research has also suggested that the impact of curricular diversity comes through two interrelated mechanisms: learning new information about the historical, social, and political conditions of racial and ethnic groups and higher‐order thinking that results from reconciling different perspectives (Mickelson, 2018).…”
Section: Toward An Ecological Framework For Studying Diversity In K12 Schoolsmentioning
confidence: 99%